2009
DOI: 10.1007/s10681-009-0025-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reduced height (Rht) and photoperiod insensitivity (Ppd) alleles on yield of wheat in contrasting production systems

Abstract: Addisu, M., Snape, J. W., Simmonds, J. R., Gooding, M. J. (2010). Effects of reduced height (Rht) and photoperiod insensitivity (Ppd) alleles on yield of wheat in contrasting production systems. Euphytica, 172 (2), 169-181Near isogenic lines (NILs) varying for reduced height (Rht) and photoperiod insensitivity (Ppd-D1) alleles in a cv. Mercia background (rht (tall), Rht-B1b, Rht-D1b, Rht-B1c, Rht8c+Ppd-D1a, Rht-D1c, Rht12) were compared for interception of photosynthetically active radiation (PAR), radiation u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 19 publications
4
57
0
Order By: Relevance
“…It was also suggested by Jones et al (2017) that the increase in flowering duration associated with Ppd-D1a would add further resilience by increasing diversity of flowering timing within a field. However, the increase in susceptibility to heat stress associated with this allele, as well as lower overall grain yield in non-stressed seasons (Addisu et al, 2010) casts doubt over the benefits that Ppd-D1a might bring under future northern European climates. Although the introduction of Rht-D1b in to Northern European wheats has increased yield through increased harvest index and reduced lodging in fertile conditions (Flintham et al, 1997), it has also been associated with some negative traits, including decreases in fertility (Law et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…It was also suggested by Jones et al (2017) that the increase in flowering duration associated with Ppd-D1a would add further resilience by increasing diversity of flowering timing within a field. However, the increase in susceptibility to heat stress associated with this allele, as well as lower overall grain yield in non-stressed seasons (Addisu et al, 2010) casts doubt over the benefits that Ppd-D1a might bring under future northern European climates. Although the introduction of Rht-D1b in to Northern European wheats has increased yield through increased harvest index and reduced lodging in fertile conditions (Flintham et al, 1997), it has also been associated with some negative traits, including decreases in fertility (Law et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the location of the cluster including old and intermediate tall cultivars on the opposite side and closer to the vector of ETo (SA) suggested that they adapted better than semi-dwarf cultivars in terms of yield to environments with high evapotranspiration before anthesis and low WI during grain filling. It is well known that the introduction of dwarfing alleles in wheat cultivars during the 20th century reduced plant height and lodging and improved the partitioning of assimilates to the grain increasing the sink capacity of the crop (Addisu et al, 2010;Álvaro et al, 2008a;Rebetzke et al, 2012;Youssefian et al, 1992), and the harvest index (Royo et al, 2007), thus allowing the crop to take advantage of more favourable conditions in terms of nutrients and water availability, and therefore crop intensification. The results of the current study indicate that when water is available after anthesis, semi-dwarf cultivars have a greater potential than the tall ones to use it in benefit of yield increases.…”
Section: Discussionmentioning
confidence: 99%
“…This work also showed that there was no signifi cant genetic change in spikes per square meter, although Taishan 23 exhibited more spikes per square meter than all other cultivars. The gain in kernels per square meter might mainly be accounted for by the introduction of the Rht-D1b and Rht8c alleles (Fischer, 1984;Addisu et al, 2010) and selection for more kernels per spike. The gain in kernels per square meter might mainly be accounted for by the introduction of the Rht-D1b and Rht8c alleles (Fischer, 1984;Addisu et al, 2010) and selection for more kernels per spike.…”
Section: Yield Potential and Its Componentsmentioning
confidence: 99%